An Education through Dance: anti-racist perspectives - Silva, Alexsander Barbozza da (2024)
This dancing/educational writing aims to propose reflections on education through dance that enables policies to confront social violence linked to racism, specifically those directed at the school scope. Therefore, this essay brings recent reflections that we have been developing in dialogue with experiences as students and artist/educators. With that in mind, we have organized this study into two umbigadas sections titled as: (1) Socio-Philosophical Conceptions of Dance Education and the Invisibility of Racial Policies, and (2) Possible Paths for Anti-Racist Education through Dance. With the completion of this work, we observed the urgency of developing Dance Education practices founded on social justice, on the transgression of white imperialism and other social violence linked to it. However, it would be necessary a self-assessment in pedagogical processes in Dance, to find ways to confront and question racist logics in Basic Education.